If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3 + -1t) + -1(4 + -3t) = 6 (3 * 5 + -1t * 5) + -1(4 + -3t) = 6 (15 + -5t) + -1(4 + -3t) = 6 15 + -5t + (4 * -1 + -3t * -1) = 6 15 + -5t + (-4 + 3t) = 6 Reorder the terms: 15 + -4 + -5t + 3t = 6 Combine like terms: 15 + -4 = 11 11 + -5t + 3t = 6 Combine like terms: -5t + 3t = -2t 11 + -2t = 6 Solving 11 + -2t = 6 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -2t = 6 + -11 Combine like terms: 11 + -11 = 0 0 + -2t = 6 + -11 -2t = 6 + -11 Combine like terms: 6 + -11 = -5 -2t = -5 Divide each side by '-2'. t = 2.5 Simplifying t = 2.5
| 14-3x=-22 | | 7m=4+5m | | a+a+2.5a=180 | | -32-9x=9+22 | | 2/3(2d+4g) | | 4/13x=1/3 | | x-9/x-4-(-8x-3)/x-4 | | x+2-3x=3+x-7x+5 | | 4(y-1)=2y+4 | | 13x+12-19x=24 | | -8+8+8g=56 | | (3)/(x^2-7x)-(5)/(x^2-49) | | 1=1-4a-6a | | 5(3)+1/2(3) | | 1/5x^2 | | 2(-4x-4)-3x=-6 | | 2x+76=180 | | 5+4w=-15 | | 4x^2+3y=439 | | 109-3x=6+10 | | 7/6r+35=-35 | | 7x-8x=-1 | | 7x-5-3+2x=15+2-4x | | 3x+7/2=2x | | 3x+29x-44=0 | | x/2+16=0 | | 5(2x-1)=55 | | 9/m+4 | | Y^3-14y^2+y-14=0 | | 9+4p-5=8p+13-3p | | y=86.010LOG(40-17)-70.041LOG(68)+36.76 | | 4x=85 |